mRNA, lncRNA, and circRNA expression profiles in a new aortic dissection murine model induced by hypoxia and Ang II - Li, Yuanyuan; Ma, Xiaozhu; Mei, Shuai; Ji, Yueping; Wang, Dong; He, Liqun; Sun, Dating; Yan, Jiangtao (Frontiers in Cardiovascular Medicine, 2022)
Background and aims: Aortic dissection (AD) is a cardiovascular emergency with degeneration of the aortic media. Mounting evidence indicates obstructive sleep apnea (OSA) as an independent risk factor for AD development with unknown mechanisms. This study aims to establish a stable murine model of OSA-related AD (OSA-AD) and uncover the potential changes in gene transcripts in OSA-AD. Methods: ApoE−/− mice were exposed to the chronic intermittent hypoxia (CIH) system combined with Ang II administration to establish the OSA-AD model. Pathological staining was performed to exhibit the physiological structure of the mouse aorta. The SBC mouse ceRNA microarray was used to identify significantly differentially expressed (DE) mRNAs, DE long-noncoding RNAs (DElncRNAs), and DE circular RNAs (DEcircRNAs) in OSA-AD tissues. Subsequently, bioinformatics analysis, including Gene Ontology (GO), Kyoto Encyclopedia of Genes and Genome (KEGG), and PPI analyses, was performed to evaluate the function of the significantly differentially expressed transcripts (DETs). The hub genes were confirmed using quantitative real-time polymerase chain reaction (qRT-PCR). Results: ApoE−/− mice exposed to CIH and Ang II showed a high ratio of aortic accident (73.33%) and significant aortic diameter dilatation (1.96 ± 0.175 mm). A total of 1742 mRNAs, 2625 lncRNAs, and 537 circRNAs were identified as DETs (LogFC ≥1.5 or ≤−1.5, P < 0.05). GO and KEGG analyses demonstrated that the DEmRNAs were most enriched in cell proliferation, migration, apoptosis, inflammation, and hypoxia-related terms, which are closely related to aortic structural homeostasis. The PPI network contained 609 nodes and 934 connections, the hub genes were highlighted with the CytoHubba plugin and confirmed by qRT-PCR in AD tissues. KEGG pathway analysis revealed that the cis-regulated genes of DElncRNAs and circRNAs-host genes were enriched in aortic structural homeostasis-related pathways. Conclusion: Our findings help establish a de novo OSA-AD animal model using ApoE−/− mice. Many DEmRNAs, DElncRNAs, and DEcircRNAs were screened for the first time in OSA-AD tissues. Our findings provide useful bioinformatics data for understanding the molecular mechanism of OSA-AD and developing potential therapeutic strategies for OSA-AD.